Effective way of learning irregular verbs - Abdukhamitova Fazilatbonu Azizovna (Genius Journals, 2022)
The main purpose of article is to introduce different and easier way of learning irregular verbs of English language.
Keywords: English grammar; irregular verb; introduce; learning